+0  
 
0
10
1
avatar+936 

The solutions to
2x^2 - 10x + 13 = -6x^2 - 18x - 15
are a+bi and a-bi, where a and b are positive. What is a\cdot b?

 Dec 15, 2023
 #1
avatar+126978 
+1

2x^2 - 10x + 13  =  -6x^2 - 18x  - 15      simplify as

 

8x^2 + 8x + 28  =  0

 

Using the quadratic formula

 

 

x  =   [ -8 ±  sqrt  [  8^2  - 4*8*28] ]          -8 ± sqrt [ -832]                 -8 ± 8sqrt (13) i

       ________________________  =   ______________  =          ______________  =

                     2 * 8                                          16                                    16

 

-1/2 ± sqrt (13) / 2  i

 

a *  b  =      -sqrt (13) / 4

 

 

cool cool cool

 Dec 15, 2023

2 Online Users

avatar